2004
DOI: 10.1175/1520-0442(2004)017<0427:mappis>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Modeled Antarctic Precipitation. Part I: Spatial and Temporal Variability*

Abstract: Surface snow accumulation is the primary mass input to the Antarctic ice sheets. As the dominant term among various components of surface snow accumulation (precipitation, sublimation/deposition, and snow drift), precipitation is of particular importance in helping to assess the mass balance of the Antarctic ice sheets and their contribution to global sea level change. The Polar MM5, a mesoscale atmospheric model based on the fifth-generation Pennsylvania State University-NCAR Mesoscale Model, has been run for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
119
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 53 publications
17
119
3
1
Order By: Relevance
“…10, Hg tot concentrations increased between 600-800 and 1000-1100 km from DC in areas characterized by steeper slopes and higher snow accumulation values. Several studies reported a gradual increase in snow accumulation from DC toward the coast (Magand et al, 2007;Verfaillie et al, 2012;Favier et al, 2013), in good agreement with a gradual increase in humidity (Bromwich et al, 2004). These results suggest that the wet deposition of Hg(II) species was enhanced near the coast, resulting in elevated Hg tot concentrations in surface snow samples.…”
Section: Transect From Central To Coastal Antarcticasupporting
confidence: 75%
“…10, Hg tot concentrations increased between 600-800 and 1000-1100 km from DC in areas characterized by steeper slopes and higher snow accumulation values. Several studies reported a gradual increase in snow accumulation from DC toward the coast (Magand et al, 2007;Verfaillie et al, 2012;Favier et al, 2013), in good agreement with a gradual increase in humidity (Bromwich et al, 2004). These results suggest that the wet deposition of Hg(II) species was enhanced near the coast, resulting in elevated Hg tot concentrations in surface snow samples.…”
Section: Transect From Central To Coastal Antarcticasupporting
confidence: 75%
“…These models are used to assess the Antarctic surface mass balance (Gallee et al 2001;Bromwich et al 2004;Van de Berg et al 2006), and therefore have a strong focus on moisture transport.…”
Section: A Description Of the Models And Simulationsmentioning
confidence: 99%
“…The results of atmospheric analyses and re-analyses products together with a dynamic retrieval method to calculate precipitation for the period 1979 to 1999 show higher amplitudes and a higher annual mean precipitation for the South Atlantic sector (65 • -75 • S, 30 • -60 • W) starting in 1988 (Fig. 16 in Bromwich et al, 2004). Considering the two peaks in 1989 and 1996, representing an increase in precipitation of 0.16 m a −1 and 0.12 m a −1 , respectively, the volume of freshwater added within one year to the surface area of 1.652×10 5 km 2 , used above to calculate the water volume on the northwestern continental shelf (<500 m), would rise to 26 × 10 9 m 3 (26 km 3 ) and 20 × 10 9 m 3 (20 km 3 ).…”
Section: Winter Conditionsmentioning
confidence: 99%